MENINGKATKAN MINAT DAN HASIL BELAJAR IPS SEJARAH MELALUI METODE KOOPERATIF TIPE TEAM ASSISTED INDIVIDUALIZATION - Joko Pramono (Universitas Sahid Surakarta, 2019)
This research is motivated by the low of the students’ interest of learning and learning outcomes. As an effort to increase students’ interest of learning and learning outcomes, Team Assisted Individualization is applied. This research was conducted in class VIII-B SMP Negeri 2 Baturetno. The aim of the research was to determine the increase the students’ interest of learning and learning outcomes in History in Social Subject. The Subject of the research was the Students of VIIIB of SMP Negeri 2 Baturetno Academic Year 2015/2016. This research is a Classroom Action Research which is done in two cycluses. Comparative Descriptive was used in Data Analysis.The result of the research are (1) The Application of the method of cooperative Team Assisted Individualization (TAI) can increase the students’ interest of learning and learning outcomes in History in Social Subject of the Students of VIII-B of SMP Negeri 2 Baturetno Academic Year 2015/2016. In Pre cyclus the interest of students learning is 58,4%, and in cyclus 1 the interest is 71,27%, and in cyclus 2 the interest is 87,41%. (2) The Application of the method of cooperative Team Assisted Individualization (TAI) can increase the learning outcomes of learning and learning outcomes in History Subject of the Students of VIII-B of SMP Negeri 2 Baturetno Academic Year 2015/2016. The result of of mastery learning shows Pre cyclus the interest of students learning is 18,5%, and in cyclus 1 the interest is 62,96%, and in cyclus 2 the interest is 88,89%